1987
DOI: 10.1177/003368828701800104
|View full text |Cite
|
Sign up to set email alerts
|

The Case for a Pedagogy of Pragmatics in Foreign or Second Language Teaching

Abstract: Not everyone can use pragmatic competence to maintain a conversa tion as a cooperative venture, and comparatively few attempts have been made to account for the development of the linguistic abilities that one may need to have in order to exhibit such competence. Yet many pragmatic components of language are probably acquired in learning sequences which correspond to successive stages in the development of children. In this article, the author (summarizes cur rent linguistic theory in the area of pragmatics,) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…While this has been an under-researched area overall, there may be some key functional differences across cultures as Blanche (1987) and Cutrone (2005) have provided anecdotal evidence of Japanese people providing unconventional backchannels in English, such as by employing continuer, understanding, agreement, and/or empathy/support type backchannels in situations when they did not understand or disagreed with what their interlocutor was saying at the time. Further, several studies involving the intercultural analyses of communication styles have shown that the Japanese L2 English speakers in these studies spoke less than NESs, did not elaborate as much, and were less likely to engage in small talk (Cutrone 2005;Hill 1990;Sato 2008).…”
Section: Functionmentioning
confidence: 99%
“…While this has been an under-researched area overall, there may be some key functional differences across cultures as Blanche (1987) and Cutrone (2005) have provided anecdotal evidence of Japanese people providing unconventional backchannels in English, such as by employing continuer, understanding, agreement, and/or empathy/support type backchannels in situations when they did not understand or disagreed with what their interlocutor was saying at the time. Further, several studies involving the intercultural analyses of communication styles have shown that the Japanese L2 English speakers in these studies spoke less than NESs, did not elaborate as much, and were less likely to engage in small talk (Cutrone 2005;Hill 1990;Sato 2008).…”
Section: Functionmentioning
confidence: 99%